Abnormalities of apoptosis of the thyroid gland cells from extratumoral microfollicular tissue - Myshunina, T.M.; Kalinichenko, O.V.; Tronko, N.D. (Experimental Oncology, 2012)
Aim: The aim of this study was to evaluate the frequency of existence of thyroid extratumoral normo- and microfollicular tissue in patients with thyroid carcinoma and peculiarities of apoptosis in mentioned tissue. Materials and Methods: Using samples of normo- and microfollicular thyroid tissue it was determined the content of fragmented DNA and intensity of stimulated internucleosomal DNA fragmentation; activities of caspase-3 and cysteine lysosomal cathepsins. Results: It was found that normofollicular tissue is observed more often in patients with nodal euthyroid goiter but microfollicular tissue is more common for patients with carcinoma. Extratumoral microfollicular tissue was found in the thyroid of patients above 50 years old mostly, and more rarely in young ones. The fragmented DNA concentration in microfollicular tissue was lower by a factor of 3.5 and intensity of stimulated internucleosomal DNA fragmentation was also decreased. Activity both of cathepsin B in lisosomes and caspase-3 in lysates of such tissue was also decreased. Conclusions: The decrease of intensity of spontaneous apoptosis and the absence of its modulation/induction following proapoptotic factors in extratumoral microfollicular thyroid tissue may be considered as a respond of the thyroid gland tissue to an existence of carcinoma.